2014
DOI: 10.1021/nl500677j
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Encapsulated DNA Origami Nanostructures for Cellular Delivery

Abstract: DNA origami structures can be programmed into arbitrary shapes with nanometer scale precision, which opens up numerous attractive opportunities to engineer novel functional materials. One intriguing possibility is to use DNA origamis for fully tunable, targeted, and triggered drug delivery. In this work, we demonstrate the coating of DNA origami nanostructures with virus capsid proteins for enhancing cellular delivery. Our approach utilizes purified cowpea chlorotic mottle virus capsid proteins that can bind a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
277
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 278 publications
(288 citation statements)
references
References 48 publications
3
277
0
8
Order By: Relevance
“…[39] Despite this progress, it has been observed that the transfection of DNA structures is generally low [40] and that these objects are prone to degradation in biological environment. [41] Nevertheless, there exist techniques to presumably enhance both stability and transfection rates of the DNA structures by utilizing different sophisticated protection and coating mechanisms, such as virus protein [42] or lipid membrane encapsulation. [43] It has also been shown that spermidine-stabilized structures could be efficiently transfected by electroporation.…”
Section: Doi: 101002/adhm201700692mentioning
confidence: 99%
“…[39] Despite this progress, it has been observed that the transfection of DNA structures is generally low [40] and that these objects are prone to degradation in biological environment. [41] Nevertheless, there exist techniques to presumably enhance both stability and transfection rates of the DNA structures by utilizing different sophisticated protection and coating mechanisms, such as virus protein [42] or lipid membrane encapsulation. [43] It has also been shown that spermidine-stabilized structures could be efficiently transfected by electroporation.…”
Section: Doi: 101002/adhm201700692mentioning
confidence: 99%
“…Mikkilä et al [47] combined virus capsid proteins (CPs) of cowpea chlorotic mottle virus (CCMV) with rectangular DNA origami sheets, resulting in CP-origami complexes with different morphologies ( Figure 1F). The highly flexible DNA rectangle could adopt either a rolled-up or a completely encapsulated form depending on the amount of CPs mixed with DNA origamis.…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 99%
“…One of them is to improve the pharmacokinetic bioavailability of the DNA-based structures in vivo. DNA origami structures can survive in cellular milieu [22] and against nucleases [20], but the circulation times of the objects could be increased by adjusting their modular properties (see above) or by creating novel protecting strategies such as protein- [47] or lipid membrane coatings [48].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations